Hybrid Narratives: Exploring Cultural Fusion in The Goats in the Cemetery by Kanogpong Songsompun - Gustiari, Amelia; Sulastri, Sulastri; Zurmailis, Zurmailis (UIN Syarif Hidayatullah Jakarta, 2023)
The short story